Experimental Rationale for Using an Eximer Laser for Preparation of Ultrathin Graft for Posterior Lamellar Keratoplasty - A. N. Pashtaev; N. P. Pashtaev; N. A. Pozdeyeva; I. V. Mukhina; S. B. Izmailova; S. A. Korotchenko; K. I. Katmakov; S. S. Alieva; K. N. Kuzmichev; B. E. Malyugin (Oftalʹmologiâ)
Purpose. To rationale experimentally the use of an excimer laser for forming an ultrathin transplant for posterior lamellar keratoplasty. Materials and methods. Atomic force microscopy was used for examination of 10 samples. Control group was 5 corneal flaps obtained by mechanical microkeratome (Moria SLK-2, France). Main group — 5 corneal flaps, obtained by microkeratome and underwent photoablation by “Microscan 500” (Optosystems, Troick, RF) excimer laser at 50 um depth. For quantification of endothelial loss 10 donor corneas (5 pairs) with viable endothelium, preserved in Borzenok—Moroz media, were used. Two groups were formed: main — 5 ultrathin transplants obtained by consistent application of microkeratome and excimer laser, control (from the paired eyes of same donors) — ultrathin transplants prepared by two cuts of microkeratome. Detection of live and dead endothelial cells (EC) was provided by Calcein Violet 450 and Propidium Iodide “vital” fluorescent dyes. Nonparametric Mann—Whitney test was used for statistical analysis. Coefficient of reliability (p < 0.05) was considered to be significant. Results. RMS (roughnessmean square) of the transplant, prepared by excimer laser was — 24.17 ± 12.4 um, and RMS of the transplant prepared by microkeratome — 22.3 ± 18.3 um. Statistical analysis did not reveal significant differences in RMS values in the mentioned groups (p > 0.05). EC death in excimer laser group was 10.35 ± 5.84 %. EC death in microkeratome group — 8.06 ± 1.31 %. No statistically reliable difference of EC death was revealed in the 2 groups (p > 0.05). Conclusions. The investigation has showed identical RMS values in the examined groups, representing high optical qualities of the transplant prepared by excimer laser. EC loss was also comparable in 2 groups. The received results indicate considerable potential of excimer laser transplants for posterior lamellar keratoplasty.